2015
DOI: 10.1192/bjp.bp.114.146324
|View full text |Cite
|
Sign up to set email alerts
|

Youth mental health after civil war: The importance of daily stressors

Abstract: BackgroundRecent evidence suggests that post-conflict stressors in addition to war trauma play an important role in the development of psychopathology.AimsTo investigate whether daily stressors mediate the association between war exposure and symptoms of post-traumatic stress and depression among war-affected youth.MethodStandardised assessments were conducted with 363 Sierra Leonean youth (26.7% female, mean age 20.9, s.d. = 3.38) 6 years post-war.ResultsThe extent of war exposures was significantly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 37 publications
7
51
1
Order By: Relevance
“…Whether this is because traumatic events set off chains of stressors or because those exposed to trauma are more likely to rate problems as more stressful and perhaps even generate problems (Neuner, 2010) is subject to some debate, and not likely solved here. Nevertheless, we believe that these findings provide network science support that joins other data gleaned from more conventional approaches to stressors and trauma supporting holistic theoretical approaches (Fernando et al, 2010; Jordans, Semrau, Thornicroft, & van Ommeren, 2014; Newnham, Pearson, Stein, & Betancourt, 2015; Rasmussen et al, 2010), and is in line with the guidelines of numerous aid organizations that recommend psychosocial professionals consider both trauma exposure and daily stressors as precipitating factors among their beneficiaries (Medicins Sans Frontiers, 2005; Inter-Agency Standing Committee, 2007). …”
Section: Discussionsupporting
confidence: 79%
“…Whether this is because traumatic events set off chains of stressors or because those exposed to trauma are more likely to rate problems as more stressful and perhaps even generate problems (Neuner, 2010) is subject to some debate, and not likely solved here. Nevertheless, we believe that these findings provide network science support that joins other data gleaned from more conventional approaches to stressors and trauma supporting holistic theoretical approaches (Fernando et al, 2010; Jordans, Semrau, Thornicroft, & van Ommeren, 2014; Newnham, Pearson, Stein, & Betancourt, 2015; Rasmussen et al, 2010), and is in line with the guidelines of numerous aid organizations that recommend psychosocial professionals consider both trauma exposure and daily stressors as precipitating factors among their beneficiaries (Medicins Sans Frontiers, 2005; Inter-Agency Standing Committee, 2007). …”
Section: Discussionsupporting
confidence: 79%
“…The findings confirmed that many youth present with comorbid problems, interpersonal conflicts, high-risk behaviors, peer influence, and difficulties accessing educational and vocational opportunities were highly salient issues [19] and that interventions should be present-day focused rather than emphasize the reprocessing past traumatic events [19,20]. Thus, the YRI was developed to embody what Herman [21] refers to as a "Stage 1" trauma intervention, intended to stabilize symptoms, ensure safety, build emotion regulation practices, and strengthen skills for managing painful memories.…”
Section: Intervention Developmentmentioning
confidence: 60%
“…The characteristics of youth in this trial were typical of those more broadly in Sierra Leone. Evidence from our ongoing longitudinal study on war-affected youth in Sierra Leone indicates a wide range of post-conflict stressors impact youths' ability to sustain improvements in psychological symptoms and functioning [20]. Unemployment, low levels of education, violence, and poverty remain persistent problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Girls were at higher risk than boys. A recent study among war affected youth from Sierra Leone highlights the role of daily stressors such as housing, food and economic security and interpersonal adversities as indirect pathways that contribute to PTSD [23]. Even among the women we studied, some of these factors seemed to be associated with a non-statistically significant trend towards PTSD (Table 2).…”
Section: Discussionmentioning
confidence: 78%